Interspecific hybrids of some East Asian representatives of the genus Chrysanthemum L. and analysis of their sustainability - A. I. Nedoluzhko (Вавиловский журнал генетики и селекции, 2016)
The garden chrysanthemum (Chrysanthemum morifolium Ramat.) is a highly demanded autumn flowering culture for parks and gardens and as cut flowers and has long, abundant and colorful flowering. The lack of winter-hardy and season-adequate flowering cultivars and poor resistance to diseases limit its distribution in most regions of Russia. The development of new plant-breeding material by artificial interspecific hybridization able to combine valuable traits of different Chrysanthemum species in a single organism is therefore of importance. Reciprocal crossing has been conducted between the species of the Manchurian (C. chanetii H. Lév., C. coreanum (H. Lév. et Vaniot) Nakai, C. maximoviczii Kom., C. naktongense Nakai, C. zawadskii subsp. acutilobum (DC.) Kitag., C. tenuisectum Kitag., C. zawadskii subsp. latilobum (Maxim.) Kitag., C. leiophyllum Nakai), Mongolian-Siberian (C. mongolicum Y. Ling, C. zawadskii Herbich) flora and interspecific hybrid forms with the involvement of subtropical Chrysanthemum species. Crossing and backcrossing of species with identical numbers of chromosomes (hexaploid × hexaploid, 2n = 54 and tetraploid × tetraploid, 2n = 36) were easy. Tetraploids × hexaploids showed good compatibility. Diploids (2n = 18) are not always compatible between themselves and are partly compatible with hexaploids. Interspecific hybrids in the first generation (F1) were characterized by phenotypic uniformity with intermediate inheritance or predominance of traits of the highploidy parent and differed in hybrid power, intensity of emergent rhizomes and complex of adaptive qualities. Multicomponent interspecific hybrids have been obtained from combinations of crossing, consisting of three different components. The selected highly decorative interspecific and multicomponent forms have promise for planting of greenery and serve as complex sources of adaptiveness for the development of garden chrysanthemum native to Russia.